Bus Monitoring System Based on Internet of Things - Zohari, Mohd Hakimi; Adam Mustaqim Azman; Mohd Hezri Mokhtar; Mohd Shamian Zainal; Lukman Iqbal Hussain (Journal of Advanced Industrial Technology and Application, 2024)
Pagoh Campus Bus Monitoring System is a system that monitors bus movement and the distance along its route to reach allocated stop area. Tracking system includes installing a digital device in the bus, with Blynk application installed on a smartphone to allow the user to monitor the bus real-time location. The project is a GPS tracking implementation based on Internet of Things. The real-time data will be sent to server and it will update the bus location periodically. The Blynk application will indicate where the vehicles are on their smartphone by using the Blynk application which is to provide the updated data to student at anywhere as long as both users and the bus have an internet connection. The Blynk server will track the position and store its information in the database. It is a real-time system as this technique transfers the data on the tracking system to the smartphone automatically. Students can use the application to get flexible in scheduling travel and decide when to board the bus. NodeMCU with built in ESP8266 microcontroller and Arduino IDE is used for both hardware and software module programming. Both of it is linked to the Blynk server and follows through the Blynk application that need to be installed in the smartphone. The user’s waiting period can be minimized. This application can be used for main monitoring program to maintain tracking of all Pagoh campus buses. The effective route management can be performed effectively through the Pagoh Campus Bus Monitoring System.